Sports Dietitians Australia position statement: Sports nutrition for the adolescent athlete - Desbrow, B.; McCormack, J.; Cox, G. R.; Fallon, K.; Hislop, M.; Logan, R.; Marino, N.; Sawyer, S. M.; Shaw, G.; Star, A.; Vidgen, H.; Leveritt, M. (International Journal of Sport Nutrition and Exercise Metabolism, 2014)
It is the position of Sports Dietitians Australia (SDA) that adolescent athletes have unique nutritional requirements as a consequence of undertaking daily training and competition in addition to the demands of growth and development. As such, SDA established an expert multidisciplinary panel to undertake an independent review of the relevant scientific evidence and consulted with its professional members to develop sports nutrition recommendations for active and competitive adolescent athletes. The position of SDA is that dietary education and recommendations for these adolescent athletes should reinforce eating for long term health. More specifically, the adolescent athlete should be encouraged to moderate eating patterns to reflect daily exercise demands and provide a regular spread of high quality carbohydrate and protein sources over the day, especially in the period immediately after training. SDA recommends that consideration also be given to the dietary calcium, Vitamin D and iron intake of adolescent athletes due to the elevated risk of deficiency of these nutrients. To maintain optimal hydration, adolescent athletes should have access to fluids that are clean, cool and supplied in sufficient quantities before, during and after participation in sport. Finally, it is the position of SDA that nutrient needs should be met by core foods rather than supplements, as the recommendation of dietary supplements to developing athletes over-emphasizes their ability to manipulate performance in comparison with other training and dietary strategies.